Reliability of the force-velocity imbalance assessment in an athletic population - Richards, B. J.; Gifford, M.; Morrison, J. K.; Willgress, S.; Noble, J.; Seaman, K. (Applied Physiology, Nutrition, and Metabolism, 2018)
The force-velocity (F-v) profile represents the relationship between optimal and actual force-velocity slopes for an athlete. From this, athletes can be stratified as either force or velocity deficient or identified as optimal (a close to optimal profile). The purpose of this study was to assess the reliability of the F-v profile in an athletic population currently performing regimented training programs. Eighteen university athletes participated in the study. Participants completed 4 testing sessions each separated by two to five days. Participants maintained their regular off-season workout routine. Each session involved a standardized warm-up and four vertical jumping conditions; bodyweight (BW), BW+15%, BW+30%, and BW+45% on a just jump mat and dumbbells. Three jumps were performed during each condition with the average of the three being utilized in the F-v equation. The intraclass correlation coefficient for Theoretical Velocity 0.946, was of "excellent reliability." Theoretical Force 0.830 and Pmax 0.865, were of "good reliability." Actual Force 0.712 and F-v imbalance (FVIMB) 0.561 were of "moderate reliability." Actual Velocity 0.422 demonstrated "poor reliability." Based on the results of the study, the F-v profile shows mixed results for reliability. Theoretical Force and Velocity as well as P max appear reliable day to day regardless of pre-test protocol. FVIMB and Actual Force have limited reliability and Actual Velocity was not reliable. Each of these variables may have been influence by the lack of a pre-assessment protocol suggesting that refrainment of lower body exercises 48 hours prior to testing may be required. Although this assessment does show a lack of reliability without a pre-assessment exercise refrainment protocol, these results demonstrate that the F-v profile assessment may be a meaningful day-to-day athlete monitoring tool to assess fatigue throughout a training program.